Big ideas in Economics: a course based on the nobel laureates in Economics - Austen, Siobhan (The University of Queensland, 2007)
This paper describes my experiences designing and teaching a course for 3rd year commerce students based around the lives and ideas of recent Nobel Laureates in economics. Most of these experiences have been positive: they have provided me with some insights into students' perceptions of mainstream economics; what students would like to learn more about in economics; and the way in which big ideas can be presented in useful and meaningful ways. These insights are likely to have relevance to other teachers of economics, working in a range of different contexts.